Plant Chromosome-Specific Probes by Microdissection of a Single Chromosome: Is That a Reality? - Soares, Fernanda Aparecida Ferrari; Carvalho, Carlos Roberto; Sattler, Mariana Cansian; Silva, Jéssica Coutinho; Pinto, Denise Eliane Euzébio; Passamani, Paulo Zanchetta; Silva, Alex Junior; Clarindo, Wellington Ronildo (Frontiers in Plant Science, 2020)
Painting plant chromosomes through chromosomal in situ suppression (CISS) hybridization has long been considered impracticable. Seeking to build specific and complex probes from a single microdissected chromosome, we employed human chromosomes as models to standardize all the necessary steps for application in plants. Human metaphases were used to define the adequate conditions for microdissection, chromosome DNA amplification and labeling through degenerate oligonucleotide-primed PCR, and in situ hybridization stringency. Subsequently, these methodologies were applied in the plant species Zea mays (chromosome 1) and Capsicum annuum (chromosome 7 or 8). The high quality of human and plant cytogenetic preparations and the meticulous standardization of each step, especially the most critical ones – microdissection and first round of DNA amplification – were crucial to eliminate the signs of non-specific hybridization and for direct application in plants. By overcoming these challenges, we obtained chromosome-specific probes, which allowed to achieve a clear and uniform painting of the entire target chromosomes with little or no background, evidencing their complexity and specificity. Despite the high amount of ubiquitous repetitive sequences in plant genomes, the main drawback for chromosome painting, we successfully employed our methodology on two plant species. Both have more than 80% repetitive sequences, which is compared to the human genome (66 – 69%). This is the first time that plant chromosome-specific probes were successfully obtained from a single A mitotic or meiotic microdissected chromosome. Thereby, we assume that chromosome painting through microdissection and CISS hybridization can now be considered a reality in the field of plant cytogenetics.